Polarographic studies on the kinetics of the electrode reaction of 4-benzoyl-1,5 diphenyl pyrazole-3-carboxylic acid - Verirsen, M; Erturan, S (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 1998)
The polarographic behavior of 4-Benzoyl-1,5 diphenyl pyrazole-3- Carboxylic acid (BDPPCA) in aqueous ethanol solution (76 % v/v) at 25 degrees C was studied as a function of pH using Mcl buffer solution. One well-defined wave was obtained in the pH range of 3.3-5.4. This wave, corresponding to two electron reduction processes, was irreversible and diffusion controlled. However, in the pH range of 5.4-7.4 a single reversible and diffusion-controlled wave involving two electrons resulted. The kinetic parameters (n(a),k(f,h)degrees) were calculated by Koutecky's method. A tentative mechanism was put forward for the reduction process of depolarizer. Furthermore, the effects of different supporting electrolytes on the kinetics of the irreversible electrode reaction of BDPPCA were investigated.
Keywords: Chemistry; Engineering